2021
DOI: 10.5812/jkums.113275
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Salivary Melatonin Levels by Scaling and Root Planing in Patients with Chronic Periodontitis

Abstract: Background: Periodontitis is a chronic inflammatory disease that causes tissue destruction due to the imbalance in the oxidant-antioxidant system. Melatonin has anti-inflammatory, antioxidant, and immune-modulatory properties and is considered to be a biomarker and diagnostic/therapeutic agent in the pathogenesis of periodontitis. Objectives: The present study aimed to evaluate the salivary melatonin level and its changes following non-surgical periodontal therapy in patients with periodontitis. Methods: In to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the reason why the melatonin level was lower in the smoking group is related to the fact that tobacco is an exogenous factor of ROS increasing [ 118 ]. According to Balaji, Purrahmani et al [ 119 ] compared the salivary level of melatonin in patients with and without periodontitis before and after the periodontal treatment. At the baseline, the melatonin level was low in patients with periodontitis compared to the healthy group.…”
Section: Studies Of Possible Biomarker For Periodontitismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the reason why the melatonin level was lower in the smoking group is related to the fact that tobacco is an exogenous factor of ROS increasing [ 118 ]. According to Balaji, Purrahmani et al [ 119 ] compared the salivary level of melatonin in patients with and without periodontitis before and after the periodontal treatment. At the baseline, the melatonin level was low in patients with periodontitis compared to the healthy group.…”
Section: Studies Of Possible Biomarker For Periodontitismentioning
confidence: 99%
“…After the non-surgical treatment, the melatonin level increased in patients affected by periodontitis. Therefore, Purrahmani [ 119 ] reported that salivary melatonin level possesses good sensitivity (80%) and specificity (80%) to evaluate the response of the periodontal treatment.…”
Section: Studies Of Possible Biomarker For Periodontitismentioning
confidence: 99%